The aging kidney and the nephrotoxic effects of mercury. (17th February 2017) - Bridges, Christy C.; Zalups, Rudolfs K.
ABSTRACT: Owing to advances in modern medicine, life expectancies are lengthening and leading to an increase in the population of older individuals. The aging process leads to significant alterations in many organ systems, with the kidney being particularly susceptible to age-related changes. Within the kidney, aging leads to ultrastructural changes such as glomerular and tubular hypertrophy, glomerulosclerosis, and tubulointerstitial fibrosis, which may compromise renal plasma flow (RPF) and glomerular filtration rate (GFR). These alterations may reduce the functional reserve of the kidneys, making them more susceptible to pathological events when challenged or stressed, such as following exposure to nephrotoxicants. An important and prevalent environmental toxicant that induces nephrotoxic effects is mercury (Hg). Since exposure of normal kidneys to mercuric ions might induce glomerular and tubular injury, aged kidneys, which may not be functioning at full capacity, may be more sensitive to the effects of Hg than normal kidneys. Age-related renal changes and the effects of Hg in the kidney have been characterized separately. However, little is known regarding the influence of nephrotoxicants, such as Hg, on aged kidneys. The purpose of this review was to summarize known findings related to exposure of aged and diseased kidneys to the environmentally relevant nephrotoxicant Hg.